A Pediatric Case of Glioblastoma Multiforme Associated With a Novel Germline p.His112CysfsTer9 Mutation in the MLH1 Gene Accompanied by a p.Arg283Cys Mutation in the TP53 Gene: A Case Report - Stajkovska, Aleksandra; Mehandziska, Sanja; Rosalia, Rodney; Stavrevska, Margarita; Janevska, Marija; Markovska, Martina; Kungulovski, Ivan; Mitrev, Zan; Kungulovski, Goran (Frontiers in Genetics, 2019)
Targeted gene panel testing has the power to interrogate hundreds of genes and evaluate the genetic risk for many types of hereditary cancers simultaneously. We screened a 13-year-old male patient diagnosed with Glioblastoma Multiforme (GBM) with the aim to get further insights into the biology of his condition. Herein, we applied gene panel sequencing and identified a heterozygous frameshift mutation c.333_334delTC; p.His112CysfsTer9 in the MLH1 gene in blood and tumor tissue accompanied by a known heterozygous missense variant of unknown significance c.847C>T; p.Arg283Cys in the TP53 gene. Parental screening revealed the presence of the same TP53 variant in the father, and the same MLH1 variant in the mother, who was in fact undergoing treatment for early-stage breast cancer at the time of her son`s unfortunate diagnosis. This case reports for the first time the co-occurrence of a genetic mutation in the MLH1 gene of the mismatch repair pathway, commonly associated with the Lynch Syndrome, accompanied by a rare variant in the TP53 gene. This report underlines the need for broad panel gene testing in lieu of single-gene or syndrome focused gene screening, and evaluation of the effects of multiple pathogenic or modifier variants on the phenotypic spectrum of the disease.